Perception Of The Fish Cultivators On Efforts Of The Cultivation The Fish In The Pond In Koto Rajo Village Kuantan Hilir Seberang District Kuantan Singingi Regency Riau Province. - Saputra, Kasbi; Bathara, Lamun; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on September 2013. The aim of this research was to describe the characteristics of the fish cultivators in Koto Rajo village, to know fish cultivators perception and to analyze the correlation between characteristics and fish cultivators perceptions on to efforts of fish’s cultivation in pond in Koto Rajo village. This research used survey method.The result of this research showed that the perception of the fish cultivators on effort of fish cultivation in pond was in good category pond Koto Rajo Village, showed that the perception the fish cultivators on effort on to effort of fish’s cultivation in pond a whole was in good category , fish cultivators had perceptions that effort of fish’s cultivation in pond had benefits for the cultivators and they agreed to develop it. Then, the correlation between internal factors and fish cultivators perception had significant correlated to perception, while ages, education, and number of dependent’s did not have significant correlated to the perception.Keyword : Perception, fish cultivators pond